Seismic Performance of Two Story Steel Building Using Shape Memory Alloys (SMAs) Bars - Jelan Hameed; Ali Laftah Abbas (Salehan Institute of Higher Education, 2019)
Shape Memory Alloys (SMA) is type of smart materials that have ability to undergo large deformation and return back to their undeformed shape through heating (shape memory effect) or removal of load (superelastic effect). This unique ability is useful to enhance behavior of structure and seismic resistance. In this paper, superelasticity (SE) effect of NiTi alloys is used to improve the structural characteristics of steel building. The finite element analysis of steel building is done using ABAQUS v.2017. In order to compare the structural behavior of the steel building equipped with Shape Memory Alloy bars at beam-column connection, three steel building was modeled with a different combination of high strength steel bars and SMA bars. The steel building was checked for time history analysis by using Vrancea 1977 earthquake data. In order to estimate the recentring ability, residual of roof displacement and energy dissipation. The steel building equipped with SMA bars shows 82.7%, 152.72% recovery in residual roof displacement for steel building equipped with 50% SMA bars and 50% HS steel bars and steel building equipped with 100% SMA bars respectively, and moderate energy dissipation. In general, the frame equipped with 50% superelastic SMA bars and 50% HS steel bars provided better seismic performance.